Evaluation of Swede score and Reid score to improve the predictive value of colposcopy and its correlation with histology - Karya, Urmila; Zehra, Azme; Rani, Anupam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cervical carcinoma is the second most common malignancy amongst women in India. It is regarded as a public health problem and a priority in cancer control programmes by the WHO. Colposcopy has proven to be very useful in identifying and guiding the biopsy of dysplastic lesion. To minimize inter-observer variation, colposcopic scoring system has been introduced. Methods: A prospective cross- sectional study including 250 women in whom the prevalence of different grades CIN was done. Co-relation of Pap (cytology) with colposcopy scoring system viz. Reid’s and Swede scores, has been made in this study. The two screening methods were compared and their statistical association with histological findings were analyzed. Results: Per speculum examination performed in 250 sexually active women with suspicious looking cervix, belonging to 25-60 years of age, with most common presenting complaints of pain abdomen (38.8%) followed by leucorrhoea, irregular cycles and Post coital bleed. Unhealthy cervix (49.2%) and persistent discharge (28%) were the most common indications for colposcopy. An assessment of both SWEDE score and Reid score as a function of histological findings was done, while Swede score of >5 showed slightly more sensitivity (100%) for diagnosing CIN1+ lesions, Reids score of >5 was more specific (100%) with a higher positive predictive value (100%) for diagnosing CIN 1, 2, 3 and invasive cervical carcinoma. There was a marked positive association between Reid score and SWEDE score. Conclusions: The colposcopic scoring systems and histopathology showed significant compliance. Predictive accuracy of colposcopy increased with increasing severity of disease.